Factors associated with cesarean delivery during labor in primiparous women assisted in the Brazilian Public Health System: data from a National Survey - Marcos Augusto Bastos Dias; Rosa Maria Soares Madeira Domingues; Arthur Orlando Corrêa Schilithz; Marcos Nakamura-Pereira; Maria do Carmo Leal (BMC, 2016)
Abstract Background The rate of cesarean delivery (CD) in Brazil has increased over the past 40 years. The CD rate in public services is three times above the World Health Organization recommended values. Among strategies to reduce CD, the most important is reduction of primary cesarean. This study aimed to describe factors associated with CD during labor in primiparous women with a single cephalic pregnancy assisted in the Brazilian Public Health System (SUS). Methods This study is part of the Birth in Brazil survey, a national hospital-based study of 23,894 postpartum women and their newborns. The rate of CD in primiparous women was estimated. Univariate and multivariable logistic regression was performed to analyze factors associated with CD during labor in primiparous women with a single cephalic pregnancy, including estimation of crude and adjusted odds ratios and their respective 95 % confidence intervals. Results The analyzed data are related to the 2814 eligible primiparous women who had vaginal birth or CD during labor in SUS hospitals. In adjusted analyses, residing in the Southeast region was associated with lower CD during labor. Occurrence of clinical and obstetric conditions potentially related to obstetric emergencies before delivery, early admission with < 4 cm of dilatation, a decision late in pregnancy for CD, and the use of analgesia were associated with a greater risk for CD. Favorable advice for vaginal birth during antenatal care, induction of labor, and the use of any good practices during labor were protective factors for CD. The type of professional who attended birth was not significant in the final analyses, but bivariate analysis showed a higher use of good practices and a smaller proportion of epidural analgesia in women cared for by at least one nurse midwife. Conclusions The CD rate in primiparous women in SUS in Brazil is extremely high and can compromise the health of these women and their newborns. Information and support for vaginal birth during antenatal care, avoiding early admission, and promoting the use of good practices during labor assistance can reduce unnecessary CD. Considering the experience of other countries, incorporation of nurse midwives in childbirth care may increase the use of good practices during labor.